(untitled) (Web of Teachers: Inderscience Research, 2024)
In this article, various factors of the environment and the impact of production activities on human health, work ability and life expectancy, the description of hygienic research and sanitation, the widely used methods of hygienic research, the use of toxicological and biological methods, hygienic characteristics, air cleanliness, industrial waste, transport, chemicals used in the home, patterns and respiratory diseases, effects on the cardiovascular system, lowering immunity, psychological effects, air exchange, providing fresh air, humidity control, thermal comfort , natural ventilation, mechanical ventilation, air cleaning systems are discussed.